Ion flow in a zeolitic imidazolate framework results in ionic diode phenomena. Issue 13 (15th January 2016) - Madrid, Elena; Buckingham, Mark A.; Stone, James M.; Rogers, Adrian T.; Gee, William J.; Burrows, Andrew D.; Raithby, Paul R.; Celorrio, Veronica; Fermin, David J.; Marken, Frank
Abstract : Ionic transport and 'ionic diode' phenomena in a zeolitic imidazolate framework (ZIF-8) are investigated by directly growing the framework as an asymmetric plug in a poly-ethylene-terephthalate (PET) film. Abstract : Ionic transport (for applications in nanofluidics or membranes) and "ionic diode" phenomena in a zeolitic imidazolate framework (ZIF-8) are investigated by directly growing the framework from aqueous Zn 2+ and 2-methylimidazole as an "asymmetric plug" into a 20 μm diameter pore in a ca. 6 μm thin poly-ethylene-terephthalate (PET) film.